Asylum Recognition Rates in Europe: Persecution, Policies and Performance - Timothy J. Hatton (Institute of Labor Economics (IZA), 2021)
A minority of applicants for asylum in Europe gain some form of recognition as refugees, and this has been a controversial issue. From the early 2000s the EU introduced a series of directives to prevent a race to the bottom in asylum policies and to harmonise policy between destination countries but the results have not been fully assessed. In this paper I examine the determinants of recognition rates for asylum applicants from 65 origin countries to 20 European destinations from 2003 to 2017. The outcomes of the EU directives have been mixed, but taken together they are associated with increased recognition rates. These made a modest contribution to the trend increase in recognition rates most of which is due to increased political terror and human rights repression in origin countries. But differences between European countries remain large, even after accounting origin country composition and for differences in the adoption of EU directives. Some of this may be accounted for by differences in bureaucratic frameworks through which policy is administered.
Keywords: F51; J15; J61; K37; 330; refugees; asylum; recognition rates